Uji Fitokimia, Toksisitas Serta Antioksidan Ekstrak Propolis Pembungkus Madu Lebah Trigona Incisa Dengan Metode 2,2-Diphenyl-1-Picrylhidrazyl (Dpph) - Aswin Thamrin; Erwin -; Syafrizal - (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2016)
Phytochemical test, test the mortality of larvae shrimp (Brine Shrimp Lethality Test) and test the antioxidant activity of secondary metabolites extract of propolis Trigona Incisa been done. Based on the test results of phytochemical screening of secondary metabolites contained in propolis extracts showed that the crude extract contains phenolic compounds and alkaloids. Ethanol fraction containing alkaloids and phenolic compounds. Ethyl acetate fraction containing alkaloid compounds. Mortality of shrimp larvae test performed to determine the toxicity values propolis extract obtained values of 50% Lethal Concentration (LC50) at 249.6079 ppm for ethanol fraction as the most active fraction. Based on the test of antioxidant activity with DPPH values obtained Inhibition Concentration 50% (IC50) in the crude extract of 139.47 ppm ethanol, ethanol fraction at 109.44 ppm, 91.42 ppm ethyl acetate fraction and vitamin C amounted to 59.44 ppm , It can be stated that the most active fraction is the fraction of ethyl acetate with IC50 value of 91.42 ppm..